Evaluation of a Comprehensive Delivery Room Neonatal Resuscitation and Adaptation Score (NRAS) Compared to the Apgar Score - Shadi R. Jurdi MD; Archana Jayaram MBBS; Adam P. Sima PhD; Karen D. Hendricks Muñoz MD, MPH, FAAP (SAGE Publishing, 2015)
This study evaluated the interrater reliability and perceived importance of components of a developed neonatal adaption score, Neonatal Resuscitation Adaptation Score (NRAS), for evaluation of resuscitation need in the delivery room for extremely premature to term infants. Similar to the Apgar, the NRAS highest score was 10, but greater weight was given to respiratory and cardiovascular parameters. Evaluation of provider (N = 17) perception and scoring pattern was recorded for 5 clinical scenarios of gestational ages 23 to 40 weeks at 1 and 5 minutes and documenting NRAS and Apgar score. Providers assessed the tool twice within a 1-month interval. NRAS showed superior interrater reliability ( P < .001) and respiratory component reliability ( P < .001) for all gestational ages compared to the Apgar score. These findings identify an objective tool in resuscitation assessment of infants, especially those of smaller gestation age, allowing for greater discrimination of postbirth transition in the delivery room.